Validation of a multiprofessional instrument for screening the risk of bronchoaspiration in a hospital environment (Research, Society and Development, 2022)
Objective: To develop and content-validate a multidisciplinary instrument for screening the risk of bronchoaspiration. Method: This is a cross-sectional, quantitative content validation study that followed the following steps: development of an instrument for screening the risk of bronchoaspiration based on a literature review and validation of this instrument according to agreement and relevance among judges. For this phase, 6 specialists in the field were invited (1 physician, 1 physiotherapist, 1 speech therapist, and 3 nurses) to evaluate the instrument and report agreement based on a Likert-type questionnaire. For the analysis of agreement between the judges, the Content Validity Index was used for each item (CVI-I) and total (CVI-T). Results: The instrument consisted of 10 items: age (≥60 years); past illness; Glasgow scale